2000
DOI: 10.1677/joe.0.1650569
|View full text |Cite
|
Sign up to set email alerts
|

The GH secretagogues ipamorelin and GH-releasing peptide-6 increase bone mineral content in adult female rats

Abstract: Growth hormone (GH) is of importance for normal bone remodelling. A recent clinical study demonstrated that MK-677, a member of a class of GH secretagogues (GHSs), increases serum concentrations of biochemical markers of bone formation and bone resorption. The aim of the present study was to investigate whether the GHSs, ipamorelin (IPA) and GH-releasing peptide-6 (GHRP-6), increase bone mineral content (BMC) in young adult female rats. Thirteen-week-old female Sprague-Dawley rats were given IPA (0·5 mg/kg per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…The mismatch between the GHS effects on body weight gain and fat accumulation in these ADX rats provides an indication that there is a fat-free component to the weight gain induced by GHS. This could reflect a GH-dependent stimulatory effect on bone and/or lean body mass (25). In the present study, the acute effects of GHRP-6 on food intake were observed in adrenal-intact rats, and this orexigenic effect was significant up to 7 h following a single peripheral injection administered during the morning, a time when the animals are normally satiated.…”
Section: Inguinalsupporting
confidence: 56%
“…The mismatch between the GHS effects on body weight gain and fat accumulation in these ADX rats provides an indication that there is a fat-free component to the weight gain induced by GHS. This could reflect a GH-dependent stimulatory effect on bone and/or lean body mass (25). In the present study, the acute effects of GHRP-6 on food intake were observed in adrenal-intact rats, and this orexigenic effect was significant up to 7 h following a single peripheral injection administered during the morning, a time when the animals are normally satiated.…”
Section: Inguinalsupporting
confidence: 56%
“…In keeping with this finding, long-term administration of ipamorelin and GHRP-6, two other GHSs, induced an increment of lumbar BMC in young intact female rats (15).…”
Section: Discussionsupporting
confidence: 72%
“…In adult rats, GHRP6 also increased body weight (Svensson et al 2000) as well as other GHSR agonists, like SM-130686 administered orally (Nagamine et al 2001) and BIM-28131 administered by s.c. injection (Strassburg et al 2008). It has been recently reported that GHSR1a agonist, a pentapeptide with D-amino acids, promotes weight gain in rats, by i.p.…”
Section: Discussionmentioning
confidence: 97%